ZAKAT AS TAX CREDIT FOR HARMONIZE FISCAL SETTING IN INDONESIA - Setianingrum, Any; Madjid, Suhirman; Asaari, Masagus (Jurnal Ekonomi Pembangunan, 2018)
This study examines the harmonization of zakah and tax synergy through the payment of zakah as tax credit in Indonesia. The research method used is case study, with data taking through document studies, literature study and indepth interviews on zakah and tax practitioners in Bekasi and Jakarta. Zakah as a tax credit is a policy that can directly reduce the amount of tax payable. The result of integration of analysis found that the tax credit from zakah can increase the acceptance in zalcat sector and tax, compared if zakah only as cost or as deductible of taxable income. Zakah as a means of tax payment control can recruit muzaki to enter groups paying zakah as well as taxes, without causing double burden for the Moslem population. The policy is in line with PSAK 101, where zakah is not involved in the income statement. The policy also helps the role of the state to allocate funds specifically to the poor in accordance with the mandate of the 1945 Constitution, which is not found in the provisions on tax allocations.